Health promotion disciplines, diversity, and development - Bunton, Robin, 1954-; Macdonald, Gordon, 1947- (Routledge, 2002)
Health Promotion is a unique multidisciplinary text appropriate for undergraduate and postgraduate students and professionals in the broad field of health and nursing.